Hepatic Hydrothorax - Krok, Karen L.; Cárdenas, Andrés (Seminars in Respiratory and Critical Care Medicine, 2012)
Hepatic hydrothorax is defined as a transudative pleural effusion, usually greater than 500 mL, in patients with portal hypertension without any other underlying primary cardiopulmonary cause. It develops most likely because of diaphragmatic defects that allow for passage of fluid from the peritoneal space to the pleural space. Because of the mechanical constraints of the thoracic cavity, this complication of portal hypertension can be challenging to treat because patients will become symptomatic when as little as 500 mL of fluid is present in the pleural space. Treatments include salt restriction, diuretics, thoracentesis, transjugular intrahepatic portosystemic shunt, video-assisted thoracoscopy, and pleurodesis. It is important to note that a chest tube is not a potential treatment option; a hepatic hydrothorax should not be treated with a chest tube unless there is frank pus in the pleural fluid or a pneumothorax is present. The ultimate treatment is a liver transplant; the development of a hepatic hydrothorax thus warrants a referral to a liver transplant center.
Keywords: ascites; cirrhosis; hepatic hydrothorax; portal hypertension; spontaneous bacterial empyema; transjugular intrahepatic portosystemic shunt (tips); pleural effusion